On becoming ethical counselors: measuring counseling ethics competency - Zakaria, Noor Syamilah; Subarimaniam, Neerushah; Wan Jaafar, Wan Marzuki; Mohd Ayub, Ahmad Fauzi; Saripan, M. Iqbal (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The Board of Counselors (Malaysia) supports advancing the registered counselors through excellence practices in counseling ethics competency. Ethics competency is salient to ensure fair and consistent ethical decision-making process; protect clients and public in general; promote practices that reflect openness to growth, change and collaboration; create and strengthen standards that reflect the society needs; respect the diversity of instructional approaches and strategies; as well as encourage program improvement and best practices. Although the significance of counseling ethics competency is evident, to date there is limited empirical research to measure counseling ethics competency, and there is no valid and reliable instrument available to measure counseling ethics competency among registered counselors. This research aims to develop an instrument to measure counseling ethics competency, determine perceived level of counseling ethics competency, and determine factors that influence counseling ethics competency. The research will involve a survey using an instrument developed during the initial stage of research and the participants will be all Malaysian registered counselors working at various settings. The researchers will employ cluster sampling in recruiting the participants. This research will describe the outline of counseling ethics competency among Malaysian registered counselors and will also provide insights for counselor educators to have more thoughtfulness in teaching and learning endeavors within the scope of counselor education training programs. Future scope may not just to focus on traits, characters and skills building to produce good counselors; but to emphasis more on ethics comprehension towards best practices of ethics application and internalization to become self-sufficient counselors.